108k views
8 votes
Solve this equation. Enter your answer in the box.
-24 + 12d= 2(d-3)+22

User SmootQ
by
5.0k points

2 Answers

9 votes


-24 + 12d= 2(d-3)+22\\\\\implies -24 +12d = 2d-6 +22\\\\\implies 12d-2d-24+6-22 = 0\\\\\implies 10d -40=0 \\\\\implies d = (40)/(10) = 4\\\\

User Titas
by
5.2k points
4 votes

Answer:


  • \boxed{\sf{d=4}}

Explanation:

In order to solve this equation, you must isolate it on one side of the equation.

Use the distributive property.

Distributive property:

⇒ A(B+C)=AB+AC

⇒ -24+12d=2(d-3)+22

Multiply.

⇒ 2(d-3)+22

⇒ 2d-2*3

⇒ 2*3=6

⇒ 2d-6

Rewrite the problem down.

⇒ 2d-6+22

⇒ -6+22=16

⇒ 2d+16

⇒ -24+12d=2d+16

Then, you add by 24 from both sides.

⇒ -24+12d+24=2d+16+24

Solve.

⇒ 12d=2d+40

Subtract by 2d from both sides.

⇒ 12d-2d=2d+40-2d

Solve.

⇒ 12d-2d=10d

⇒ 10d=40

Divide by 10 from both sides.

⇒ 10d/10=40/10

Solve.

Divide the numbers from left to right.

⇒ 40/10=4


\Longrightarrow:\boxed{\sf{d=4}}

  • Therefore, the correct answer is d=4.

I hope this helps! Let me know if you have any questions.

User Franssu
by
5.5k points